Integration of Sensor Networks with Cloud Computing - Medina, Santiago (2020)
This article presents a possible approach for the integration of wireless sensor networks with applied IoT (Internet of Things) platforms related to Fog Computing concepts. Several ideas are presented related to: a) definition of the main characteristics to be considered in the deployment of sensor networks, b) evaluation of alternatives for combining wireless communication technologies and, c) experimentation with different IoT platforms for local data preprocessing that will then optimize the data flow of information to the cloud.